A Web 2.0 GIS G-Government website for the Gauteng City-Region - Wray, Chris (My University, 2012)
As the world advances towards an increasingly connected and spatially enabled Internet society, governments need to adopt new Web GIS technologies to become more efficient and connected with their citizens. Responding to this need, the Gauteng City-Region Observatory (GCRO) GIS website was developed to provide a g-government application for Gauteng City-Region (GCR), using a combination of GIS and Web 2.0 technologies. The website visualises governmental data in new dynamic ways, using a rich Internet application (RIA) viewer that integrates data from various sources including Google Maps. The Technology Acceptance Model (TAM) was used to determine the success of the GCRO g-government website by measuring user acceptance at the prototype and implementation stages of the project. High acceptance scores were achieved by the GCRO GIS website, thus confirming that the GCRO staff and local and provincial government in the GCR are ready to utilise g-government.